Development of a milk-type beverage using mongo (Phaseolus Aureus Roxb.) flour - Baronia, Esther C. (1978)
Mongo (Phaseolus aureus, Roxb.) flour was used as the raw material to develop a milk-type beverage. The first phase of the study which involved the determination of an acceptable formulation for the beverage resulted as follows: 4% mongo flour, 6% sucrose, 6% butter, 0.1% vanillin, 0.1% carboxymethylcellulose (CMC) and 83.8% water. The second phase dealt with the pasteurization of the beverage. Based on the microbiological, physico-chemical tests and sensory evaluation conduction, pasteurization at 85°C for 15 seconds gave a relatively stable product.